The Impact of Anemia During Pregnancy on the Childbirth Process and Postpartum Recovery - Fransisca, Andriani, Junay Darmawati, Lidya; Adriani; Darmawati, Junay (STIKes Budi Mulia Sriwijaya, 2026)
The results of the 2023 Indonesian Health Survey (SKI) stated that 27.7% of pregnant women in Indonesia experienced anemia. Pregnant women with anemia are at risk of experiencing complications during labor and the postpartum period, such as prolonged labor, weak uterine contractions, delayed wound healing, and postpartum hemorrhage. The purpose of this study was to determine the relationship between the labor process and postpartum recovery with anemia during pregnancy. This study used an analytical survey method with a cross-sectional approach involving 57 respondents. Samples were collected using the accidental sampling technique. The results of the chi-square test showed that there was a relationship between the labor process and postpartum recovery with anemia during pregnancy, with a ρ-value of 0.003 and 0.003. Based on the results of the study, it can be concluded that anemia during pregnancy has an impact on the labor process and postpartum recovery.